Asesmen Program Asistensi Mengajar Satuan Pendidikan Berbasis Kognitif, Afektif, Dan Psikomotorik Di Mts Negeri 9 Jombang - Rizki, Restu Budiansyah; Haris, Abdul; Hudayana, Nur Alawi; Asari; Hasanah, Uswatun; Hindun; Triwijayati, Luluk Habibah; Hakim, Luqman (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
This study aims to evaluate the teaching program assessment in an educational unit as part of the Merdeka Belajar-Kampus Merdeka (MBKM) curriculum. This research is a case study involving 5th-semester students participating in a teaching assistance program, with a total of 11 student participants. Data collection methods included direct observation and assessment documentation by supervising school teachers. Data analysis used a qualitative-quantitative percentage approach. The results showed that among the three assessment domains—cognitive, affective, and psychomotor—the lowest scores were in the affective domain (3.55), while the highest scores were in the psychomotor domain (3.58). Individually, Student 7 achieved the highest overall score (3.77) compared to the others. These findings indicate that the 11 participating students need to improve their affective domain skills in learning and teaching processes. All three domains (cognitive, affective, and psychomotor) will serve as essential preparation for these student practitioners when entering the real workforce throughout their professional lives.